Does inhibitory control training improve health behaviour? A meta-analysis. Issue 2 (2nd April 2016) - Allom, Vanessa; Mullan, Barbara; Hagger, Martin
Abstract : Objectives : Inhibitory control training has been hypothesised as a technique that will improve an individual's ability to overrule impulsive reactions in order to regulate behaviour consistent with long-term goals. Methods : A meta-analysis of 19 studies of inhibitory control training and health behaviours was conducted to determine the effect of inhibitory control training on reducing harmful behaviours. Theoretically driven moderation analyses were also conducted to determine whether extraneous variables account for heterogeneity in the effect; in order to facilitate the development of effective intervention strategies. Moderators included type of training task, behaviour targeted, measurement of behaviour and training duration. Results : A small but homogeneous effect of training on behaviour was found, d +   = 0.378, CI95  = [0.258, 0.498]. Moderation analyses revealed that the training paradigm adopted, and measurement type influenced the size of the effect such that larger effects were found for studies that employed go/no-go (GNG) training paradigms rather than stop-signal task paradigms, and objective outcome measures that were administered immediately yielded the largest and most consistent effects on behaviour. Conclusions : Results suggest that GNG inhibitory control training paradigms can influence health behaviour, but perhaps only in the short-term. Future research is required to systematically examine the influence of training duration, and the longevity of the training effect. Determining these factors could provide the basis for cost-effective and efficacious health-promoting interventions.